2022
DOI: 10.1590/2318-0331.272220220012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of rating curve uncertainty in flood frequency analysis

Abstract: Maximum flows are often estimated from flood frequency analysis, by means of the statistical fitting of a theoretical probability distribution to maximum annual flow data. However, because of the limitations imposed by the practice of at-site flow measurement, empirical models are applied as the rating curve for estimating streamflow. These curves are approximations of the actual flows and incorporate different sources of uncertainty, especially in the extrapolation portions. These uncertainties are propagated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Moreover, the estimation and the propagation of the various sources of uncertainty throughout the FFA chain is not straightforward to achieve. Several papers performed an integrated analysis in which both rating curve parameters and flood frequency distribution were estimated ; Steinbakk et al (2016); Vieira et al (2022)). They concluded that accounting for rating curve uncertainties may notably widen the total uncertainty of flood quantiles.…”
Section: Usefulness Of Disentangling the Various Sources Of Uncertain...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the estimation and the propagation of the various sources of uncertainty throughout the FFA chain is not straightforward to achieve. Several papers performed an integrated analysis in which both rating curve parameters and flood frequency distribution were estimated ; Steinbakk et al (2016); Vieira et al (2022)). They concluded that accounting for rating curve uncertainties may notably widen the total uncertainty of flood quantiles.…”
Section: Usefulness Of Disentangling the Various Sources Of Uncertain...mentioning
confidence: 99%
“…Therefore, it is possible to distinguish the effects of independent and systematic stage errors on streamflow uncertainty. , Steinbakk et al (2016), and Vieira et al (2022) performed an integrated analysis in which both rating curve parameters and flood frequency distribution are estimated. These studies highlighted the importance of considering rating curve uncertainty for design flood estimations and concluded that, under some conditions, accounting for rating curve uncertainty may notably widen the uncertainty intervals around flood quantiles.…”
Section: Introductionmentioning
confidence: 99%